2016
DOI: 10.4103/0974-9233.194078
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of reading performance with minnesota low vision reading charts in patients with age-related macular degeneration

Abstract: PURPOSE:To evaluate the reading performance using the Minnesota low vision reading (MNREAD) charts, of patients with age-related macular degeneration (AMD) who use low vision aid (LVA) devices.MATERIALS AND METHODS:This prospective study enrolled 27 patients with AMD. Distance visual acuity (VA) was evaluated with a distance chart designed for patients with low vision. Near vision and reading performance were evaluated with the Turkish version of the MNREAD charts. Unaided vision and vision with LVA devices an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The authors concluded that the effects of visual cortex a-tDCS on peripheral reading varied for different writing systems. However, reading abilities vary widely in AMD patients depending on their remaining vision and the location of their preferred retinal locus ( Fletcher et al, 1999 ; Altinbay et al, 2016 ; Farzaneh et al, 2021 ). It has also been argued that AMD is accompanied by negative peripheral retinal manifestations because of the increased prevalence of peripheral autofluorescence abnormalities [see Pivovar and Oellers (2021) for a review].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the effects of visual cortex a-tDCS on peripheral reading varied for different writing systems. However, reading abilities vary widely in AMD patients depending on their remaining vision and the location of their preferred retinal locus ( Fletcher et al, 1999 ; Altinbay et al, 2016 ; Farzaneh et al, 2021 ). It has also been argued that AMD is accompanied by negative peripheral retinal manifestations because of the increased prevalence of peripheral autofluorescence abnormalities [see Pivovar and Oellers (2021) for a review].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the effects of visual cortex a-tDCS on peripheral reading varied for different writing systems. However, reading abilities vary widely in AMD patients depending on their remaining vision and the location of their preferred retinal locus [19][20][21] . It has also been argued that AMD is accompanied by negative peripheral retinal manifestations because of the increased prevalence of peripheral autofluorescence abnormalities (see Pivovar & Oellers 22 for a recent review).…”
Section: Introductionmentioning
confidence: 99%